Effect of Physical Exercise on Insulin Sensitivity and the Modifiable Cardiovascular Risk Factors of Patients with T2DM: A Systematic Review - Wahyu Sukma Samudera; Ferry Efendi; Retno Indarwati (Universitas Airlangga, 2020)
Introduction: This study was undertaken to verify effect of regular exercise training on insulin sensitivity and the modifiable cardiovascular risk factors, and to determine if there was any effect from the different regular exercises. Methods: A database search using PRISMA examined articles from Scopus, ScienceDirect and ProQuest. The inclusion criteria were that the article used a randomized controlled trial within the last 10 years, that the respondents were people with type 2 diabetes mellitus and that only physical exercise was the intervention involved. In total, 1,303 articles were screened and 16 articles were included that fit the criteria of inclusion in this systematic review. Results: Based on the review of the 15 articles, the findings show that regular exercise training has some benefits related to glycemic control. It can reduce insulin resistance, plasma insulin, fasting blood glucose, postpandrial blood glucose and hbA1c. . Moreover, physical exercise has other benefits for people with type 2 diabetes mellitus, such as an increased peak oxygen consumption (VO2 peak) and decreased c-reactive protein (CRP) level. Conclusion: Regular exercise training has benefits for people with type 2 diabetes mellitus and it can allow them to achieve of optimal glycemic control by improving insulin resistance and decreasing the cardiovascular risk factors. Physical exercise such as combined exercises (aerobic and resistance exercise) or a single exercise such as aerobic exercise can be recommended to improve insulin sensitivity and the modifiable cardiovascular risk factors in patients with T2DM.